Penerapan Metode Double Moving Average Untuk Memprediksi Penjualan Tiket Bus Sinar Jaya Po Tambun - Tundo, Tundo; Nugroho, Agung Yuliyanto; Saidah, Andi (Universitas Wahid Hasyim, 2025)
The Sinar Jaya Autobus Company (PO) is one of the buses engaged in the tourism business that sells and provides community needs such as bus tickets. This PO requires forecasting in data processing to produce accurate reports. The reason for this is because PO Bus Sinar Jaya in determining the demand for bus tickets cannot predict availability. Based on these reasons, the design of this system uses the Double Moving Average (DMA) forecasting method for the forecasting process in determining the amount and type of availability that will be sold for the following month. By using this calculation method it is hoped that the owner of PO Sinar Jaya will further optimize the things that can be detrimental to this PO in operating. If sales increase each month, using the DMA method, sales predictions for the next three months can be determined, the higher the number of ticket requests on the PO Sinar Jaya Bus, so that the forecasting results can help the PO to avoid running out of tickets according to consumer demand. Based on the research that has been carried out, it can be concluded that the Sinar Jaya PO Tambun bus ticket sales forecast using the Double Moving Average (DMA) method obtained the smallest MAPE value calculation results in order 2, namely 0.004599299 and the smallest MAPE value in order 3, namely 0.000614191. Comparison of the results of MAPE value calculations to determine the accuracy of forecasting results carried out with order 2 and order 3, it is proven that order 3 is more accurate for determining the error percentage results in this study.